The Relationship Between Age, Gender And The Incidence Of Acute Appendicitis In Naval Hospital dr. Oetojo Sorong Period January 2021 – June 14 2022 - Achmad Ngutro Fuad, Romadhan; Papendang , Harry Allan; Siwi Hartanto , Agus Purna (Sean Institute, 2022)
Appendicitis is a condition which inflammation occurs in the vermiform appendix, commonly known by the public as appendicitis. Appendicitis can also cause acute inflammation most commonly in the right area of the abdominal cavity and the most common cause of emergency abdominal surgery. Based on data in the city of Sorong, West Papua province, this disease is one of the diseases with a high incidence in the surgical section. Based on a preliminary study conducted in 2019, At Sele Be Solu Hospital, Sorong City, there were 70 cases of postoperative appendicitis in just 3 months in 2019. There has been no previous research in Sorong regarding the relationship between age, gender and the incidence of appendicitis. I. Objective: to determine the relationship between age and gender with the incidence of acute appendicitis. Methods : This study was conducted on patients diagnosed with acute appendicitis at the Naval Hospital dr. Oetojo Sorong from January 2021-14 June 2022 on 71 respondents with a cross sectional design study using secondary data. Results: The proportion of high risk age (20-40 years) is 54.9%, and low risk age (<20 or >40 years) is 45.1%. Female gender is 63.4%, and male sex is 36.6%, the incidence of acute appendicitis is 58.9%, and perforated appendicitis is 21.1%. Analysis of the relationship between age and the incidence of appendicitis was obtained with a value of p=0.013, the relationship between sex and the incidence of appendicitis was obtained with a value of p=0.007. Conclusion: there is a statistically significant relationship, namely age and gender with the incidence of acute appendicitis